Atlantic Crossings: Biosocial Interventions in African Diasporic Bioarchaeological Thought and Practice - Cunningham, Andreana S (American journal of biological anthropology, 2025)
The African diaspora, or the mass displacement of Africans and their descendants as a result of colonial slave trading, continues to be a topic of methodological and theoretical interest in biological anthropology and bioarchaeology. However, the legacies of racist and exploitative research that are inherent to diasporic burial contexts have prompted questions about the futures of diasporic bioarchaeological practice. This paper presents a biosocial integrative framework as an intervention toward interdisciplinary study of African diasporic biosocial variation. Framing the sea as a site of rupture, possibility, and interconnectivity serves as a theoretical foundation for this framework to outline both the diversity and complications in analyzing enslavement contexts. In operationalizing biosocial integrative approaches, the framework emphasizes critical interrogation and deconstruction of traditional modes of measurement. These considerations are applied to two diasporic island case studies in 19th century Barbados and St. Helena, sites comprising enslaved and "Liberated African" groups, respectively. The case studies reflect the ways that notions of birthplace can profoundly shape modes of racialization and agency. In Barbados, this emerged in the disparity between creole and African birthplace, while in St. Helena this was demonstrated in biosocial stratification and prominent Southeastern African origins. The case studies reveal ways that shifting 19th century coercive labor systems corresponded with changes to migration flows and Afro-descendants' origins. More broadly, the framework and case studies demonstrate how biosocial integrative approaches may glean a more holistic understanding of historic Afro-descendant variation.